Determinants of Patient Satisfaction in Healthcare Industry in Delhi using PLS-SEM - Bansal, Neha; Narwal, Mahabir; Prinkle, Prinkle (Journal of Health Management, 2024)
The healthcare industry in India has advanced significantly in recent years. As a result of corporatisation, hospitals' classes and quality have significantly changed in modern times. The intangible nature of healthcare services imposes a great challenge
Keywords: Administrative Services; Doctor Services; Healthcare Industry; Nurse Services; Pathological Services; Patient Satisfaction